Pengaruh Cash Holding, Debt Maturity, Manajemen Aset dan Manajemen Risiko terhadap Kinerja Keuangan - Tiara Debby Silviana; Yuyun Isbanah (Universitas Negeri Surabaya, 2025)
Companies are highly dependent on financial performance because it provides information about how well or poorly a company is performing. The focus of this study is to determine how the financial performance of energy companies listed on the Indonesia Stock Exchange during the period 2021–2023 is influenced by cash holdings, debt maturity, asset management, and risk management. The type of data used is quantitative data sourced from secondary data. Energy companies listed on the Indonesia Stock Exchange during the 2021–2023 period constitute the population in this study. The sample was selected using purposive sampling, with a total of 66 companies. Data were calculated using STATA 17, and panel regression was used for analysis. The results indicate that cash holdings and asset management have a positive and significant impact on financial performance. Conversely, debt maturity and risk management do not have a significant impact on financial performance. Companies in the energy sector need to maintain and improve cash management and asset utilization to enhance financial performance.